Validation of Problem-Based Learning Teaching Modules on Momentum and Impulse to Improve Students' Critical Thinking Skills - Tresnane Suandti Sekarani; Hamdi Akhsan; Kistiono Kistiono (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to validate a Problem-Based Learning (PBL) teaching module on Momentum and Impulse material to improve the critical thinking skills of Grade XI students. The validation ensures the module's feasibility before implementation in the classroom. Methodology: This research and development (R&D) study used the Four-D Model (Define, Design, Develop, Disseminate), limited to the development stage. Validation involved four experts who assessed the module using a validation questionnaire. Data were analyzed quantitatively based on content, construct, language, presentation, and assessment criteria. Main Findings: The module received an average validity score of 89%, categorized as "Valid" without revision. The highest scores were in learning construct/model (92%) and assessment (91%). All aspects is content, language, presentation, and graphics were deemed suitable for classroom use, supporting the module's readiness for implementation. Novelty/Originality of this study: This study offers a PBL-based teaching module specifically designed for the Merdeka Curriculum, integrating critical thinking indicators and Pancasila Student Profile values. It addresses the lack of contextual, structured physics teaching tools and provides a validated, practical resource for teachers to enhance students' critical thinking through real-world problems.